Utilisation et rôles des exemples lors d'enseignements universitaires de chimie - Isabelle Kermen (Nantes Université, 2016)
A qualitative study was conducted by means of interviews of eight chemistry teachers in two universities. It determined the uses and the functions that the teachers assign to examples in their teaching. The teachers surveyed agree about the place and caracteristics of examples, about their cognitive, pedagogical, motivational or mediative functions On the contrary they disagree when it comes to designate what is done in practical sessions, which are essentially examples for some and concrete situations for others. The analysis of the justifications given by the teachers shows that choosing to use a specific example or a certain type of example is due to various influences which partially condition the teachers' practices. The mediative role toward the industrial world seems more important in master or professional degree but no real case studies including several types of skills and knowledge are being conducted.